2017
DOI: 10.5513/jcea01/18.2.1919
|View full text |Cite
|
Sign up to set email alerts
|

Response of spring wheat to different soil and foliar fertilization

Abstract: In the years 2013-2015 a field experiment was carried out, whose aim was to determine the response of spring wheat cultivar Arabella to different levels of soil fertilization with NPK and foliar feeding Plonvit Zboża. Higher level of soil fertilization with NPK caused an increase in the LAI (Leaf Area Index), MTA (Mean Tip Angle) and SPAD (Soil Plant Analysis Development) indices in comparison to lower fertilization level. The applied soil fertilization and foliar application did not differentiate the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
(10 reference statements)
3
5
1
Order By: Relevance
“…Yasser and Naheif (2018) noted that the variation of yield and its attributes in response to increasing N fertilization levels in wheat varieties, to the genetic constitution ability of the genotypes to benefit from the amount of N applied. These results are in agreement with those mentioned by Atia et al (2016), Jarecki et al (2017), Solomon and Anjulo (2017) and Morsy et al (2018). Moreover, some genotypes gave highly significantly grain yield/m 2 .…”
Section: Grain Yield/msupporting
confidence: 93%
“…Yasser and Naheif (2018) noted that the variation of yield and its attributes in response to increasing N fertilization levels in wheat varieties, to the genetic constitution ability of the genotypes to benefit from the amount of N applied. These results are in agreement with those mentioned by Atia et al (2016), Jarecki et al (2017), Solomon and Anjulo (2017) and Morsy et al (2018). Moreover, some genotypes gave highly significantly grain yield/m 2 .…”
Section: Grain Yield/msupporting
confidence: 93%
“…The variant with the use of the bacterial fertilizer's composition ensured the better way of grains development and increasing the weight of 1,000 seeds to 28.2 g (+2.5 g to control). The results for the weight of 1,000 seeds in this experiment are far above those obtained by Volkogon (2006), Jarecki et al (2017) reported that in spring wheat three-time foliar fertilization increased weight of 1,000 seeds and yield.…”
Section: Resultscontrasting
confidence: 45%
“…The importance of efficient N fertilization for yield and quality of spring wheat has been highlighted by many researchers. Among the factors that have a significant impact are the dose of N fertilization (Jaćimović et al, 2008;Staugaitis et al, 2017) source of N fertilizer (Jarecki et al, 2017), timing of N application (Rawluk et al, 2000;Woolfolk et al, 2002;Karamanos et al, 2005), culture rotation (Kaerner, 1999;Halvorson et al, 2000), frequency of rainfall and temperature during the growing season (Zhang and Oweis, 1999). A recommended technique for synchronizing the N supply with the wheat N demand is split application of the N fertilizer (Nyiraneza et al, 2012).…”
Section: Methodsmentioning
confidence: 99%